STUDI PENGARUH KONDISI TANAH WILAYAH PESISIR PANTAI AMAL TERHADAP TAHANAN PEMBUMIAN ELEKTRODE PASAK 1,5 METER GEDUNG LABORATORIUM TEKNIK UNIVERSITAS BORNEO TARAKAN - Achmad Budiman (Jurnal Harpodon Borneo, 2017)
Earthing systems are less well able to cause damage to electrical equipment. The risks are more current can not be optimally channeled back to earth. The smaller the resistance value, The better the earthing system. In certain soil conditions, grounding resistance value is also influenced by the depth of planting electrodes. The measurement results one ground rod resistance value with a length of 1.5 m, a diameter of 0.045 m, a depth of 3 m in Building Engineering Laboratory of the Borneo Tarakan University obtained value R (earth) = 12.76 Ω, while the calculation of R (earth) = 12.85 Ω with the average value of muddy clay resistivity (ρ) = 38.58 Ω-m. For the attainment of the grounding resistance value ≤ 5 Ω as required in the General Terms Electrical Installation (PUIL 2000) will require a minimum of three ground rod.